1997
DOI: 10.1177/104063879700900301
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Differentiation of Primate α-herpesviruses by PCR

Abstract: Abstract.simplex virus types 1 and 2 [HSV1, HSV2], green monkey simian agent 8, baboon herpesvirus 2 [HVP2], and macaque B virus [BV]) was developed utilizing the polymerase chain reaction (PCR). PCR primers were located in conserved regions of the gene encoding the glycoprotein B, which flanks an intervening region that is highly divergent among the 5 viruses. Amplified PCR products from the 5 viruses were readily differentiated by their unique restriction enzyme digestion patterns. No variation in digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…For many years the baboon virus HVP2 was assumed to be identical to SA8 (9,11,12,17). However, more recent studies show that, while very closely related to SA8, baboon isolates represent a distinct virus (1,7). Similar to the case for BV in macaques, more than 90% of adult baboons show serological evidence of infection with HVP2, and clinically evident disease due to HVP2 is uncommon (6,27).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…For many years the baboon virus HVP2 was assumed to be identical to SA8 (9,11,12,17). However, more recent studies show that, while very closely related to SA8, baboon isolates represent a distinct virus (1,7). Similar to the case for BV in macaques, more than 90% of adult baboons show serological evidence of infection with HVP2, and clinically evident disease due to HVP2 is uncommon (6,27).…”
mentioning
confidence: 87%
“…Swab samples were processed and inoculated onto Vero or DBG3 cells as described previously (2,6). All suspected HVP2 isolates were confirmed to be HVP2 by PCR and sequencing as described previously (1,2). Origins and properties of HVP2 strains used in this study are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Comparative studies of HSV detection have demonstrated that virus isolation lacks the sensitivity of PCR for the detection of virus shedding (Coyle et al, 1999;Madhavan et al, 1999;Wald et al, 1997). Traditional PCR assays for B virus detection have been described (Black & Eberle, 1997;Hirano et al, 2000;Scinicariello et al, 1993;Slomka et al, 1993). This study represents the first description of a real-time, quantitative PCR assay for B virus and its use for detection of B virus shedding from mucosal sites in macaques.…”
Section: Discussionmentioning
confidence: 99%
“…Although B virus isolation is generally considered the standard for virus detection, studies with other viruses indicate that virus isolation is a less sensitive method than other techniques such as PCR (Cone et al, 1994;Wald et al, 1995). Nonquantitative PCR techniques have been described for B virus (Black & Eberle, 1997;Scinicariello et al, 1993;Slomka et al, 1993;Weigler et al, 1995). A sensitive, quantitative PCR-based assay to determine the presence of B virus DNA would help assess both the frequency and the titre of shed viral DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Several two-step PCR methods, which make use of restriction fragment length polymorphism (RFLP) after PCR amplification, have been developed to detect and identify BV (1,16,17,18). As previously reported, we established a PCR method to amplify a DNA segment of the glycoprotein G (gG) gene (US4 gene) from a BV strain isolated from a rhesus macaque by adding betaine (1-carboxy-N,N,N-trimethylmethanammonium inner salt) to the PCR mixture (9).…”
mentioning
confidence: 99%